The Banking Functions of the Hungarian Urban Network in the Early 20th Century - Gál, Zoltán (Discussion Papers, 2012)
The paper examines an equally important topic for the finance, regional science and banking history. It adopts modern methodological approaches to reveal the links between regional, urban development and banking. The paper presents the regional distribution of the bank capital, the territorial differences in savings and loan outstanding, and the factors affecting the geographical distribution of local-regional banking centres. The paper examines the impact of the Hungarian banking system on regional and urban development in the early 20th century, when local banks were important territorial elements of the financial space developing close links to regional economic structures. It is based on previous research on territorial distribution of banking functions adopted the methodology of Christaller's Central Place Theory. The basic concept of the study is that there is closer connection not only between the banking sector and the economy as a whole, but between the banking sector and urban development as well. This is coincidental with the argument of the American historical geography school, which says that the features of the urban network are in strong correlation with the spatial structure of banking system. We considered the spatial breakdown of capital flows as one of the most important indicators of regional and urban transformation. In the age of the Austro-Hungarian Union (1867-1918), the universal banking system was primarily based on the „unit banking”, including locally and regionally embedded commercial banks, saving banks and credit unions. Investigations carried out at the level of historical regions and urban network made it possible to perform a comparative analysis of the different regions’ banking network, economic and urban development.